Immune Checkpoint Inhibitors Regulate K+ Channel Activity in Cytotoxic T Lymphocytes of Head and Neck Cancer Patients - Gawali, Vaibhavkumar S.; Chimote, Ameet A.; Newton, Hannah S.; Feria-Garzón, Manuel G.; Chirra, Martina; Janssen, Edith M.; Wise-Draper, Trisha M.; Conforti, Laura (Frontiers in Pharmacology, 2021)
Programmed death receptor-1 (PD-1) and its ligand (PD-L1) interaction negatively regulates T cell function in head and neck squamous cell carcinoma (HNSCC). Overexpression of PD-1 reduces intracellular Ca2+ fluxes, and thereby T cell effector functions. In HNSCC patients, PD-1 blockade increases KCa3.1 and Kv1.3 activity along with Ca2+ signaling and mobility in CD8+ peripheral blood T cells (PBTs). The mechanism by which PD-L1/PD-1 interaction regulates ion channel function is not known. We investigated the effects of blocking PD-1 and PD-L1 on ion channel functions and intracellular Ca2+ signaling in CD8+ PBTs of HNSCC patients and healthy donors (HDs) using single-cell electrophysiology and live microscopy. Anti-PD-1 and anti-PD-L1 antibodies increase KCa3.1 and Kv1.3 function in CD8+ PBTs of HNSCC patients. Anti-PD-1 treatment increases Ca2+ fluxes in a subset of HSNCC patients. In CD8+ PBTs of HDs, exposure to PD-L1 reduces KCa3.1 activity and Ca2+ signaling, which were restored by anti-PD-1 treatment. The PD-L1-induced inhibition of KCa3.1 channels was rescued by the intracellular application of the PI3 kinase modulator phosphatidylinositol 3-phosphate (PI3P) in patch-clamp experiments. In HNSCC CD8+ PBTs, anti-PD-1 treatment did not affect the expression of KCa3.1, Kv1.3, Ca2+ release activated Ca2+ (CRAC) channels, and markers of cell activation (CD69) and exhaustion (LAG-3 and TIM-3). Our data show that immune checkpoint blockade improves T cell function by increasing KCa3.1 and Kv1.3 channel activity in HNSCC patients.